Analysis of Mathematical Thinking Habits of Mathematics Education Students - Hayati, Rizki; Hartatiana, Hartatiana; Agustiani, Riza (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2023)
Humans are individuals who experience changes in adaptation from students to students with different learning systems. Each adaptation experienced by students will differ fromone individual to another. The purpose of this study is to find out the habits of mathematical thinking of students in mathematics education study program from one of the State University in Palembang. Respondents of this study were 50 students of the mathematics education study program at the state university. This study uses quantitative approachs. The design used is survey research. Survey was conducted by using closed questionnaire. The questionnaire consist of 32 statements regarding the habit of mathematical thinking in learning mathematics. The results of this study indicated that students are in the good category as much as 68.43%. For the indicators of flexible thinking and metacognitive thinking, each has a percentage score of 69.90% and 71.36%, all of which are in the good category. Meanwhile, thinking and communicating clearly and precisely has a percentage score of 63.6% in the sufficient category. It is hoped that further research will use the habit of mathematical thinking as a learning strategy to provide innovation in learning mathematics so that it has a positive effect on students to develop and improve the habits of mathematical thinking in learning mathematics